Pemanfaatan Limbah Padat Sari Apel sebagai Bahan Baku Cuka Apel Menggunakan Metode Backslop - Alvianty Novitasari; Warkoyo Warkoyo; Sri Winarsih (Food Technology and Halal Science Journal, 2019)
Solid wasted of apple cider containing a lot of compounds such as carbohydrates, glucose, malic acid, and flavonoids. The purpose of this research is to utilize the solid wasted of apple cider as the raw material of apple vinegar. The fermentation process of making apple vinegar in this research using the backstop method. This research consists of 2 steps of the fermentation process. The first step of fermentation using yeast to transform sugar into alcohol. Second step fermentation is a continuance of first step fermentation with the addition of apple vinegar backstop culture which contain Acetobacter aceti with density 4 x 107cfu / ml to transform alcohol to acetic acid. This research uses simple and factorial Randomized Block Design (RBD). Fermentation phase I using simple RBD with the proportion of apple raw material (solid wasted of apple cider: apple) 100% : 0%; 75%: 25%; 50%: 50%; 25%: 75% as factor I. Fermentation phase II using factorial RBD with the combination of factor I and the addition of apple vinegar backstop with concentration 5%, 10%, and 15% as factor II. The results showed that during the first step fermentation process the raw material proportion of apple (solid wasted of apple cider: apple) affected total soluble solids, pH value, and alcohol content. Fermentation phase II showed an interaction between the proportion of the raw material of apple (apple cider waste: apple) and the addition of backstop apple vinegar concentration to total dissolved solids, alcohol content, acetic acid, except pH value. The best results showed treatment with apple material proportion (25% solid wasted of apple cider: 75% apple) and addition of apple vinegar backstop concentration 15 % produce 4.6 g / 100ml acetic acid, 4% soluble solids total, pH value of 3.4 and alcohol residue of 0% (v/v), with colorful organoleptic results quite appealing, the scent is sufficient, and preferences are favored by the panelists.